Secondhand Smoke Exposure Impairs Ion Channel Function and Contractility of Mesenteric Arteries. Issue 5 (19th August 2021) - Le, Thanhmai; Martín-Aragón Baudel, Miguel; Syed, Arsalan; Singhrao, Navid; Pan, Shiyue; Flores-Tamez, Victor A; Burns, Abby E; Man, Kwun Nok Mimi; Karey, Emma; Hong, Junyoung; Hell, Johannes W; Pinkerton, Kent E; et al.
Abstract: Cigarette smoke, including secondhand smoke (SHS), has significant detrimental vascular effects, but its effects on myogenic tone of small resistance arteries and the underlying mechanisms are understudied. Although it is apparent that SHS contributes to endothelial dysfunction, much less is known about how this toxicant alters arterial myocyte contraction, leading to alterations in myogenic tone. The study's goal is to determine the effects of SHS on mesenteric arterial myocyte contractility and excitability. C57BL/6J male mice were randomly assigned to either filtered air (FA) or SHS (6 h/d, 5 d/wk) exposed groups for a 4, 8, or 12-weeks period. Third and fourth-order mesenteric arteries and arterial myocytes were acutely isolated and evaluated with pressure myography and patch clamp electrophysiology, respectively. Myogenic tone was found to be elevated in mesenteric arteries from mice exposed to SHS for 12 wk but not for 4 or 8 wk. These results were correlated with an increase in L-type Ca 2+ channel activity in mesenteric arterial myocytes after 12 wk of SHS exposure. Moreover, 12 wk SHS exposed arterial myocytes have reduced total potassium channel current density, which correlates with a depolarized membrane potential ( Vm ). These results suggest that SHS exposure induces alterations in key ionic conductances that modulate arterial myocyte contractility and myogenic tone. Thus, chronic exposure to an environmentally relevant concentration of SHS impairs mesenteric arterial myocyte electrophysiology and myogenic tone, which may contribute to increased blood pressure and risks of developing vascular complications due to passive exposure to cigarette smoke. Abstract : Secondhand smoke alters vascular smooth muslce ion channel function and vascular tone. Figure created with BioRender.com